The Cross-linguistic Influence of Iraqi Arabic on Acquiring English Grammar - Mohammed Taher Jasim ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2021)
This study examines one of the most frequent problems, which is the cross-linguistic impact of first language (henceforth L1), in acquiring the grammar of the foreign language (henceforth F2). An experimental investigation, which took more than three months, was undertaken on 85 ILEs . An analysis of the data of present simple tense formulae was conducted on 315 excerpts produced by ILEs. The scenarios from each topic were extracted in four stages of the study. A quantitative analysis reveals the cross-linguistic influence of Iraqi Arabic on obtaining linguistic elements of English in general, and particularly in acquiring present simple tense.